PENGARUH PENGEMBANGAN PRODUK DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN PADA KFC SUDIRMAN PEKANBARU - Fitrika Manurung; Meyzi Heryanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research was conducted at KFC Sudirman Pekanbaru, as for the purpose of this study to determine the effect of product development and brand image on consumer's satisfaction at KFC Sudirman Pekanbaru. Product development as an independent variable (X1) and brand image as an independent variable (X2) while the customer's satisfaction as the dependent variable(Y).The problem in this research is the target and actual sales of KFC Sudirman Pekanbaru that never hit the target. Seen from the percentage of sales that fluctuate or experience ups and downs of product purchase within the last 4 years. The sample used in this study of 100 respondents from the population using the formula slovin. As well as a sampling technique by purposive sampling. Questioner. The result of data collection through analysis using multiple linear regression, t test, and the test so it can be seen that f variable product development positively affects customer's satisfaction, brand image that administration significant effect on customer satisfaction, and significant influence between product development and the image of the product to consumer's satisfaction.Keywords: Product Development, Brand and Customer's Satisfaction